Language learning self-efficacy beliefs of German as foreign/second language learners: A scale development study - Ferdiye Çobanoğulları (Journal of Pedagogical Research, 2022)
Students' self-efficacy is a crucial factor in learning foreign/second language. Although a growing body of literature has drawn attention to the self-efficacy in various fields, very few studies have addressed this issue in the field of foreign language and especially German learning. The purpose of this paper was to develop a reliable and valid tool for measuring self-efficacy beliefs of German learners. A total of 205 students (154 Female and 51 Male) studying in the German language education department participated in the study. After the data collection, exploratory factor analysis and confirmatory factor analysis were performed to determine the validity and reliability of the scale. The Cronbach Alpha value of the developed scale was found to be 0.928, which is quite high. The explained variance value of the factors was found to be 62.943, which indicates a high validity. As a result of the analysis, a 23-item and 3-dimensional scale was developed. In conclusion, the developed scale is a valid and reliable tool for measuring language learning performance, linguistic skills, and learning confidence in the language learning process in the context of self-efficacy belief.